Depressive Symptom Profiles Predict Specific Neurodegenerative Disease Syndromes in Early Stages - Shdo, Suzanne M.; Ranasinghe, Kamalini G.; Sturm, Virginia E.; Possin, Katherine L.; Bettcher, Brianne M.; Stephens, Melanie L.; Foley, Jessica M.; You, Shou-Chin Christine; Rosen, Howard J.; Miller, Bruce L.; Kramer, Joel H.; Rankin, Katherine P. (Frontiers in Neurology, 2020)
Background: During early stages, patients with neurodegenerative diseases (NDG) often present with depressive symptoms. However, because depression is a heterogeneous disorder, more precise delineation of the specific depressive symptom profiles that arise early in distinct NDG syndromes is necessary to enhance patient diagnosis and care. Methods and Findings: 564 participants self-reported their depressive symptoms using the Geriatric Depression Scale (GDS), including 111 healthy older control subjects (NC) and 453 patients diagnosed with one of six NDGs who were at the mild stage of disease (Clinical Dementia Rating Scale <2) (186 Alzheimer’s disease [AD], 76 behavioral variant frontotemporal dementia [bvFTD], 52 semantic variant primary progressive aphasia [svPPA], 46 non-fluent variant PPA [nfvPPA], 49 progressive supranuclear palsy syndrome [PSPS], 44 corticobasal syndrome [CBS]). The GDS was divided into subscales based on a previously published factor analysis, representing 5 symptoms (dysphoria, hopelessness, withdrawal, worry, and cognitive concerns). Mixed models were created to examine differences in depression subscale by group, and logistic regression analyses were performed to determine if patterns of depressive symptoms could predict a patient’s NDG syndrome. PSPS patients presented with a hopeless, dysphoric, and withdrawn pattern, while patients with CBS presented with a similar but less severe pattern. Worry was a key symptom in the profile of patients with svPPA, while ADs only had abnormally elevated cognitive concerns. Depressive profile accurately predicted NDG diagnosis at a rate of between 70% - 84% accuracy. Conclusions: These results suggest that attention to specific depressive symptom profile can improve diagnostic sensitivity and can be used to provide more individualized patient care.